Distribution of manganese in peat deposit of Tomsk region - Viktor Sergeyevich Arkhipov; Vilis Bernatonis (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The aim of the research is to study manganese distribution in peat deposits of Tomsk region. The patterns in distribution of iron, calcium and some trace elements in peat deposits of Tomsk regionwere previously identified. The aim of the work Relevance. The development of peat resources of Tomsk region will allow manufacturing peat products for agriculture, medicine and power engineering. The skillful use of peat requires the knowledge of not only the technological properties of peat, but also its mineral composition, especially the content of biologically active elements, which include manganese. Methods of research. During the research, fieldwork was conducted in peat bogs of the Tomsk region. The authors have selected stratified samples of peat on 8 swamps of taiga zone in Tomsk region and surveyed horse watershed mires and fens river valleys. Manganese content in peat was determined by manganese ions oxidation in nitric acid solution with ammonium persulfate in the presence of silver nitrate. The concentration of permanganate ions in solution was determined on photocolorimeter KLF-2MP with 50 mm cuvette at a wavelength of 530 nm. Results. It was found out that manganese content in peat deposits of taiga zone in Tomsk region varies from 20…50 to 900...950 mg/kg of dry peat. The minimum content of manganesewas detected in the centers of the upland watershed wetlands, and the maximum content was detected in lowland swamps of river valleys. On the periphery of large wetland systems the transient and low-lying deposits with manganese content of 200...300 mg/kg are widely spread. The peat layers with lime mineralizationare the most manganese-rich. Conclusions. The distribution of manganese in the bogs and systems of varying complexity obeys the laws of landscape-geochemical systems. The geochemically conjugated autonomous and subordinate units related to migration flows and wetland soil and groundwaterare among them.